2009
DOI: 10.3390/ijerph6092456
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Health: Inequalities and Potential Determinants

Abstract: Understanding social inequalities in health is of great importance; it provides the conceptual frame for investigating the social factors that affect health, together with empirical evidence for improving population health. Individual and socioeconomic data, disease related conditions and self rated health (SRH) ratings were collected from a representative sample of 1,000 participants in order to study health inequalities in Greece. 20.8% of men and 37.2% of women reported poor health status. Significant inequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
1
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 33 publications
5
62
1
5
Order By: Relevance
“…The results of a study conducted in Greece by Alexopoulos et al on a group of 1000 subjects indicate that 20.8% of males and 37.2% of females regard their health as unsatisfactory. It is strongly related to sex, age insurance coverage and chronic diseases [12]. A similar observation has been made in the authors' own study in which the respondents' age and education affected their health.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of a study conducted in Greece by Alexopoulos et al on a group of 1000 subjects indicate that 20.8% of males and 37.2% of females regard their health as unsatisfactory. It is strongly related to sex, age insurance coverage and chronic diseases [12]. A similar observation has been made in the authors' own study in which the respondents' age and education affected their health.…”
Section: Discussionsupporting
confidence: 82%
“…Results of the studies confirm that self-rated health remains not only an essential and reliable indicator of health of a population but is also a crucial morbidity and mortality predictor. It plays a role in assessing the need for medical care [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, an over-representation of children in our data cannot be excluded since one of the three hospitals in the study was a paediatric one. There was also a male preponderance in our data which could partly be attributed to social factors in Greece [28]. Urban/rural distribution is a research field that needs attention in order to understand the epidemiology of any infectious disease, however different social structures across countries could make this element difficult to interpret [29].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Sweden among an adult population found that MS pain was closely associated with poor self-reported health and a lower quality of life (Molarius and Janson 2002). Similarly, studies in Canada and Greece found that MS pain was among the most important indicators related to fair or poor self-rated health (Perruccio et al 2007, Alexopoulos andGeitona 2009). Physical health is a central component of self-perceptions of health and well-being (Jylha 2009), which likely explains why people experiencing MS symptoms have lower health status than those who are asymptomatic.…”
Section: Comparisons and Contributions To The Literaturementioning
confidence: 99%